Rapid Recovery of Postoperative Pulmonary Function in Patients With Lung Cancer and Influencing Factors - Fuzhi, Yang; Dongfang, Tang; Wentao, Fu; Jing, Wang; Yingting, Wu; Nianping, Mo; Wen, Gao; Xiaoyong, Shen (Frontiers in Oncology, 2022)
Among malignant tumors, lung cancer has the highest morbidity and mortality worldwide. Surgery is the first-line treatment for early-stage lung cancers, and has gradually advanced from conventional open-chest surgery to thoracoscopic pneumonectomy. Additionally, increasingly smaller surgical incisions and less surgical trauma have resulted in reduced pulmonary function damage. Previous studies have found that the level of pulmonary function loss and recovery is significantly correlated with postoperative complications and the quality of life. Thus, an accurate assessment of the preoperative pulmonary function and effective rehabilitation of postoperative pulmonary function are highly important for patients undergoing lung surgery. In addition, pulmonary function assessment after pulmonary rehabilitation serves as an objective indicator of the postoperative pulmonary rehabilitation status and is crucial to facilitating pulmonary function recovery. Furthermore, a complete preoperative assessment and effective rehabilitation are especially critical in elderly patients with pulmonary tumors, poor basic physiological functions, comorbid lung diseases, and other underlying diseases. In this review, we summarize the clinical significance of pulmonary function assessment in patients undergoing lung cancer surgery, postoperative changes in pulmonary function, effective pulmonary function rehabilitation, and the influencing factors of pulmonary function rehabilitation.